Privatization and Restructuring in Central and Eastern Europe - Anderson, Robert E.; Dejankov, Simeon; Pohl, Gerhard; Claessons, Stijn (World Bank, Washington, DC, 2012)
One of the most important policy questions in the transition economies is what governments can do to speed the restructuring of firms and thus hasten the transition to a mature market economy. The authors report on a study that provides some answers. Privatization encourages restructuring if it is rapid and comprehensive and leads to concentrated ownership. Privatization also promotes restructuring because privatized firms are more likely than state-owned enterprises to exercise wage restraint--and wage restraint is vital to free up the necessary internal finance. But policies that increase bank lending to firms, such as debt forgiveness and recapitalization, may do more harm than good. The safest course is to recapitalize banks only as part of privatization and to encourage negotiations for financial restructuring only after the banks are privatized.